Determination of natural radioactivity in irrigation water of drilled wells in northwestern Saudi Arabia. (February 2016) - Alkhomashi, N.; Al-Hamarneh, Ibrahim F.; Almasoud, Fahad I.
Abstract: The levels of natural radiation in bedrock groundwater extracted from drilled wells in selected farms in the northwestern part of Saudi Arabia were addressed. The investigated waters form a source of irrigation for vegetables, agricultural crops, wheat, and alfalfa to feed livestock consumed by the general public. Information about water radioactivity in this area is not available yet. Therefore, this study strives to contribute to the quality assessment of the groundwater of these wells that are drilled into the non-renewable Saq sandstone aquifer. Hence, gross alpha and beta activities as well as the concentrations of 224 Ra, 226 Ra, 228 Ra, 234 U, 238 U, and Utotal were measured, compared to national and international limits and contrasted with data quoted from the literature. Correlations between the activities of the analyzed radionuclides were discussed. The concentrations of gross alpha and beta activities as well as 228 Ra were identified by liquid scintillation counting whereas alpha spectrometry was used to determine 224 Ra, 226 Ra, 234 U and 238 U after separation from the matrix by extraction chromatography. The mean activity concentrations of gross α and β were 3.15 ± 0.26 Bq L −1 and 5.39 ± 0.44 Bq L −1, respectively. Radium isotopes ( 228 Ra and 226 Ra) showed mean concentrations of 3.16 ± 0.17 Bq L −1 and 1.12 ± 0.07 Bq L −1, respectively, whereas lower levels of uranium isotopes ( 234 U and 238 U) were obtained. Graphical abstract: Highlights: Natural radiation in bedrock groundwater in northwestern Saudi Arabia were assessed. Groundwater form an irrigation source for agricultural crops consumed by the public. Gross α and β concentration and concentrations of Ra and U isotopes were determined. Liquid scintillation counting and alpha spectrometry were used in the measurements. Higher concentrations of Ra isotopes were obtained in relative to U isotopes.